2010
DOI: 10.1111/j.1365-2249.2010.04252.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro exposure of human fibroblasts to local anaesthetics impairs cell growth

Abstract: SummaryLidocaine, bupivacaine or ropivacaine are used routinely to manage perioperative pain. Sparse data exist evaluating the effects of local anaesthetics (LA) on fibroblasts, which are involved actively in wound healing. Therefore, we investigated the effects of the three LA to assess the survival, viability and proliferation rate of fibroblasts. Human fibroblasts were exposed to 0·3 mg/ml and 0·6 mg/ml of each LA for 2 days, followed by incubation with normal medium for another 1, 4 or 7 days (group 1). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 53 publications
3
58
0
1
Order By: Relevance
“…While our study found results similar to previous studies on the effects of bupivacaine and lidocaine on wound healing [30][31][32][33][34][35][36][37][38][39][40][41] , no significant difference was found between tramadol and the control group. The antibacterial properties of local anesthetics and other agents used in wound infiltration are important.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…While our study found results similar to previous studies on the effects of bupivacaine and lidocaine on wound healing [30][31][32][33][34][35][36][37][38][39][40][41] , no significant difference was found between tramadol and the control group. The antibacterial properties of local anesthetics and other agents used in wound infiltration are important.…”
Section: Discussionsupporting
confidence: 73%
“…Other research found that lidocaine and bupivacaine inhibited collagen synthesis in fibroblast tissue cultures, and had cytotoxic effects on different cell lines [30][31][32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations